Existence of Solutions for Mixed Fractional Integro-differential Equations in Banach Spaces - Karthikeyan, P.; Keerthivasan, K. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we study the existence and uniqueness of solutions for mixed fractional integro-differential equations combined with integral boundary conditions of slit-strips type. Uniqueness results are proved using the classical contraction mapping principle and D.O'Regan's fixed point theorem is used to establish the existence results. To illustrate our main findings, we present an example.